(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Factors contributing to learning achievement and learning strategy for supporting students in functioning academically has remained a major theme in educational research. In this article, we put forth a metacognitive learning strategy in developing students’ academic self-concept and learning achievement. Seventy-two high school students were subjected to either metacognitive learning strategy or conventional learning strategy and their academic self-concept as well as learning achievement was then evaluated after learning. Metacognitive learning strategy significantly improved students’ academic self-concept and learning achievement. Interconnection between academic self-concept and learning achievement in metacognitive learning strategy scheme was also found.